2005
DOI: 10.1007/s11046-004-9483-1
|View full text |Cite
|
Sign up to set email alerts
|

Keratinophilic fungi isolated from hospital dust and soils of public places at Gulbarga, India

Abstract: Keratinophilic fungi were isolated from corridor dust of 11 hospitals and soils of 21 public places using a hair baiting technique. A total of 41 species belonging to 24 genera were recovered. Among the dermatophytes and related species, Microsporum gypseum was predominant, followed by Chrysosporium keratinophilum, Trichophyton mentagrophytes, M. nanum and Ch. tropicum. Other species were represented by 32 species belonging to 21 genera. Most of the species isolated are known to be agents of human and animal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 29 publications
1
20
0
3
Order By: Relevance
“…But these fungi were not reported from indoor hospital and house dust nor was their hair perforating ability determined. However, Vidyasagar et al [7] reported keratinophilic fungi from hospital dust and soils of public places from Gulburga, India. Kushwaha [8] reported dermatophytes and keratinophilic fungi from hospital waste collected outside.…”
Section: Discussionmentioning
confidence: 99%
“…But these fungi were not reported from indoor hospital and house dust nor was their hair perforating ability determined. However, Vidyasagar et al [7] reported keratinophilic fungi from hospital dust and soils of public places from Gulburga, India. Kushwaha [8] reported dermatophytes and keratinophilic fungi from hospital waste collected outside.…”
Section: Discussionmentioning
confidence: 99%
“…The keratinophilic fungi and aerobic Actinomycetes are distributed worldwide (8)(9)(10)(11) which is more attracted Iranian researches in recent years (4,(12)(13)(14)(15). In this study, we surveyed city park soils of Gorgan (a northern province of Iran) for determine the identities and diversity of soil aerobic Actinomycetes, keratinophilic and non-keratinophilic fungi.…”
Section: Objectivesmentioning
confidence: 99%
“…Urbano Rural actividad de los niños en las aulas, aportan el material queratínico necesario para mantener la presencia y diversidad de estos hongos en zonas menos antropofizadas (Otcenasek et al, 1967;Dominik et al, 1973;Van Gelderen & Elias, 1978;Marchisio, 1986;Zaror et al, 1986;Piontelli & Toro, 1987;Caretta et al, 1976Caretta et al, , 1989Mercantini et al, 1995;Armes & Hilda, 1998;Mangiaterra et al, 2000;Shadzi et al, 2002;Vidyasagar et al, 2005). Los integrantes del género Chrysosporium obtuvieron los mayores aislamientos y el mayor número de especies en ambas zonas, pero con un notable aumento de frecuencia de presencia y diversidad en la zona rural.…”
Section: H R Y S O S P O R I U M K E R a T I N O M Y C E S M I C R unclassified
“…(Alvarez & Bracalenti 1984;Piontelli et al 1984;Armes & Hilda, 1998;Mangiaterra et al, 2000;Shadzi et al, 2002;Vidyasagar et al, 2005). Los suelos de los establecimientos educacionales y áreas circundantes, son frecuentemente fuente de substratos queratínicos aportados por animales domésticos, aves y presencia humana (estudiantes), presentan gran interés ecológico y epidemiológico (Marchisio et al, 1986;Armes & Hilda, 1998).…”
Section: Introduccionunclassified